AN ANALYSIS OF BILATERAL TRADE BETWEEN INDIA AND KOREA - Shanmugam, Vidhya; N, Asha; C, Samanvitha; Murthy, Lahari N; Thangam, Dhanabalan (The journal of contemporary issues in business and government, 2021)
India and Republic of Korea (Korea) have been engaging in the bilateral trade relationship from 1962. Though the trade relationship exists for 56 years between the countries, very limited researches have conducted on the trade relationship between the countries. Hence, the present study made an attempt to fill the gap in the literature by assessing and understanding trade pattern of two countries. Based on the existing studies and the availability of data, qualitative methods have been utilized to analyze composition of trade between India and Korea. Further, the trade intensity index, intra industry trade index, and revealed comparative advantage index have been utilized to assess the dynamics of the bilateral trade between India and Korea. It is observed from the trade intensity index that, India’s trade with Korea is less than it should and thus India has a great scope to expand its trade with Korea. There are 9 commodity groups alone having highest intra industry index value and the remaining smaller values indicates less trade between the countries. Comparative advantage index shows that there were no overlaps in two countries trade; therefore two countries have a chance to increase their trade with each other. Since very limited studies have analyzed bilateral trade between India and Korea, the present work assesses the trade pattern between the countries, and the factors motivating such trade. Moreover, the findings would be helpful to promote the commercial as well as economic relations between the countries.